ICD-10 anaphylaxis algorithm and the estimate of vaccine-attributable anaphylaxis incidence in Medicare. Issue 38 (7th September 2021) - Goud, Ravi; Thompson, Deborah; Welsh, Kerry; Lu, Michael; Loc, Julie; Lindaas, Arnstein; Arya, Deepa; Chillarige, Yoganand; Wernecke, Michael; MaCurdy, Thomas E.; Kelman, Jeffrey A.
Highlights: Anaphylaxis can occur after vaccine, drug, food, or environmental exposures. Validated ICD-10 claims algorithms can help characterize anaphylaxis risk. We describe construction and validation of an anaphylaxis ICD-10 algorithm in Medicare Fee For Service. The algorithm revealed vaccine-attributable anaphylaxis is rare in Medicare Fee For Service. Abstract: Background: Anaphylaxis is a rare, serious allergic reaction. Its identification in large healthcare databases can help better characterize this risk. Objective: To create an ICD-10 anaphylaxis algorithm, estimate its positive predictive values (PPVs) in a post-vaccination risk window, and estimate vaccination-attributable anaphylaxis rates in the Medicare Fee For Service (FFS) population. Methods: An anaphylaxis algorithm with core and extended portions was constructed analyzing ICD-10 anaphylaxis claims data in Medicare FFS from 2015 to 2017. Cases of post-vaccination anaphylaxis among Medicare FFS beneficiaries were then identified from October 1, 2015 to February 28, 2019 utilizing vaccine relevant anaphylaxis ICD-10 codes. Information from medical records was used to determine true anaphylaxis cases based on the Brighton Collaboration's anaphylaxis case definition. PPVs were estimated for incident anaphylaxis and the subset of vaccine-attributable anaphylaxis within a 2-day post-vaccination risk window. Vaccine-attributable anaphylaxis rates in Medicare FFS were also estimated. Results: The study recorded 66, 572, 128 vaccinations among 21, 685, 119 unique Medicare FFS beneficiaries. The algorithm identified a total of 190 suspected anaphylaxis cases within the 2-day post-vaccination window; of these 117 (62%) satisfied the core algorithm, and 73 (38%) additional cases satisfied the extended algorithm. The core algorithm's PPV was 66% (95% CI [56%, 76%]) for identifying incident anaphylaxis and 44% (95% CI [34%, 56%]) for vaccine-attributable anaphylaxis. The vaccine-attributable anaphylaxis incidence rate after any vaccination was 0.88 per million doses (95% CI [0.67, 1.16]). Conclusion: The ICD-10 claims algorithm for anaphylaxis allows the assessment of anaphylaxis risk in real-world data. The algorithm revealed vaccine-attributable anaphylaxis is rare among vaccinated Medicare FFS beneficiaries.